(untitled) (Web of Teachers: Inderscience Research, 2025)
This study explores research-based teaching principles that support effective instruction for English learners (ELs) in university contexts. As global mobility increases, higher education institutions host growing numbers of linguistically diverse students who require not only language acquisition support but also pedagogical strategies that promote academic integration, motivation, and engagement. Drawing on established frameworks in cognitive science, sociocultural theory, and second language acquisition (SLA), this paper identifies and analyzes seven core principles of "smart teaching" tailored to ELs. Using qualitative content analysis of classroom observations and instructor interviews across three universities, the findings reveal that inclusive practices, scaffolded feedback, and contextually relevant tasks significantly enhance ELs’ academic performance and confidence. Implications for language curriculum development and teacher training are also discussed.